2020
DOI: 10.1007/s10964-019-01191-z
|View full text |Cite
|
Sign up to set email alerts
|

How Age and Disclosures of Sponsored Influencer Videos Affect Adolescents’ Knowledge of Persuasion and Persuasion

Abstract: This study examines the effects of age (early versus middle adolescence) combined with the content of disclosures for sponsoring in online influencer videos on adolescents' knowledge of persuasion and on persuasion. An experiment was conducted among a sample of 406 adolescents (167 early adolescents aged 12-14 years, mean age 12.85, SD = 0.14, 53% female; and 239 middle adolescents, aged 15-16 years, mean age 14.36, SD = 0.13, 59% female). The results show that early adolescents need extensive information (dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 43 publications
1
22
0
2
Order By: Relevance
“…Therefore, in the new market situation, when promoting products, services or brands has never been so difficult, organizations have begun to look for alternative methods of influencing consumers [27]. One of the most important trends is the use of the concept of influencer marketing [28][29][30]. This concept is understood as "marketing practice that takes advantage of well-followed online users, who are able to influence consumers' attitudes and decision-making processes in favor of brands or ideas" [31].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in the new market situation, when promoting products, services or brands has never been so difficult, organizations have begun to look for alternative methods of influencing consumers [27]. One of the most important trends is the use of the concept of influencer marketing [28][29][30]. This concept is understood as "marketing practice that takes advantage of well-followed online users, who are able to influence consumers' attitudes and decision-making processes in favor of brands or ideas" [31].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, a large body of empirical disclosure studies has robustly demonstrated the effect of disclosures on marketing fairness constructs (Boerman et al, 2015b;Van Reijmersdal & van Dam, 2020). However, many factors moderate the effect size of disclosures (Spielvogel et al, 2019).…”
Section: Marketing Disclosure and Young Consumersmentioning
confidence: 99%
“…Marketing researchers use arguments related to process and outcome unfairness when discussing (disguised, covert, masked or native) marketing techniques targeted at young consumers, but they do not always clearly and explicitly prescribe to one view (Rowthorn, 2019;Wojdynski & Evans, 2019). Overall, empirical researchers of young consumers aim to improve non-evaluative fairness constructs, such as improved recognition of the commercial intent, and stay mostly normatively agnostic about evaluative outcome constructs, such as desired attitude and behavioral change, unless there is a social consensus on the promoted products being clearly harmful to young consumers, such as unhealthy foods or alcohol (Coates et al, 2019;Van Reijmersdal & van Dam, 2020). Indeed, studies have demonstrated that young consumers susceptibility to advertising can be decreased by, for example, instructing them about the persuasive and selling intent of advertisements (e.g., Buijzen, 2007).…”
Section: Ethics Of Young Consumer Marketingmentioning
confidence: 99%
See 2 more Smart Citations